Evaluation of Effect of β-Lactam Antibiotics on Suppression of Different Strains of Agrobacterium tumefaciens and on Wheat Mature Embryo Culture: Effect of b-lactam antibiotics on wheat embryo - Adel Yarizade,; Farzaneh Aram,; Ali Niazi,; Younes Ghasemi, (Iranian Journal of Pharmaceutical Sciences, 2012)
The efficiency of four β-lactam antibiotics meropenem, imipenem, ceftazidime and ceftriaxone were tested on three strains of Agrobacterium, tumefacience LBA4404, AGL0 and C58 and were compared with the commonly used antibiotic, cefotaxime. Meropenem exhibited the most effective antibacterial activity against Agrobacterium tumefacience LBA4404, AGL0 and C58. In addition to the high levels of activity of the antibiotics meropenem and imipenem on Agrobacterium inhibition (MIC less than 10 mg.l-l and MBC less than 150 mg.l-l), they allowed a high rate of shoot formation and had no significant negative effects on shoot and root weights of wheat explants. Therefore, they can be recommended for Agrobacteriummediated transformation projects for wheat.